(3EfHGg GdQhGI Ydi CfHGA GdfMGIs - (3Ydj Hf jhSa Hf EHQGgje GdTjHGfj GdbaWj, CHh GdMSf, LeGd GdOjf,J (B646 (3g` s
(3ChdgG (B:s
(3CeG HYO abO cGf HYV efJMdi UfGYI GdJUfja bO ELRi PcQ CNHGQ GdfMGI QZH ai LeYgG s
(3BNQgG (B:s
(3hgPG cJGH de jXgQ dg PcQ dG HGdYQGb hdG HGdTGe heUQ hGXf Cf eUfag bQjH GdYgO hGddg CYde Je GdLRA GdKGdK s
(3fSNI KGfjIs
(3hgj Yf fSNI WhHbHh SQGi (B2858s
(3jHJOF HChd GdcJGH hjfJgi Edi JQLeI GdahQis
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs